Empirical treatment of neonatal sepsis: are the current guidelines adequate?. Issue 1 (28th June 2010) - Muller-Pebody, B; Johnson, A P; Heath, P T; Gilbert, R E; Henderson, K L; Sharland, M; ,
Abstract : Objectives: To use national laboratory surveillance data to determine whether pathogens responsible for neonatal bacteraemia were sensitive to nationally recommended antibiotic regimens. Design: All reports of neonatal bacteraemia received by the Health Protection Agency's voluntary surveillance scheme in England and Wales from January 2006 until March 2008, were extracted from the database. Organisms were ranked by frequency, and proportions susceptible to antimicrobials recommended for empirical treatment of neonatal sepsis were determined. Results: There were 1516 reports of bacteraemia for neonates <48 h old (early-onset) and 3482 reports for neonates 2–28 days old (late-onset). For early-onset bacteraemia, group B streptococcus (GBS) was the most frequent pathogen (31%) followed by coagulase-negative staphylococci (CoNS; 22%), non-pyogenic streptococci (9%) and Escherichia coli (9%). For late-onset bacteraemia, CoNS were isolated most frequently (45%), followed by Staphylococcus aureus (13%), Enterobacteriaceae (9%), E coli (7%) and GBS (7%). More than 94% of organisms (early-onset) were susceptible to regimens involving combinations of penicillin with either gentamicin or amoxicillin, amoxicillin combined with cefotaxime or cefotaxime monotherapy. More than 95% of organisms (late-onset) were susceptible to gentamicin with either flucloxacillin or amoxicillin and amoxicillin with cefotaxime, but only 79% were susceptible to cefotaxime monotherapy. Conclusions: Current guidelines for empirical therapy in neonates with sepsis are appropriate. However, gentamicin-based regimens should be used in preference to cefotaxime-based treatments, because of lower levels of susceptibility to cefotaxime and the need to avoid exerting selective pressure for resistance. Surveillance data linked to clinical data should further inform rational antibiotic prescribing in neonatal units.